Pop knitting : bold motifs using color & stitch - Christoffersson, Britt-Marie (Interweave Press, 2012)
"Celebrated author Britt-Marie Christoffersson has studied color and texture in knitting for more than 25 years. Pop Knitting showcases her intensive work, demonstrating how minimal ingredients can be combined in seemingly endless ways to create striking, graphic knitted fabrics. Using a variety of innovative stitch manipulation techniques, this book explores how to construct highly textured fabrics and gorgeous knitted strandwork. You'll also learn how to create knitted fabrics with holes, pleats, double-fabrics, and more. Knitters of all skill levels will love the projects and inspiration Christofferson presents and the aesthetic masterpiece of Pop Knitting will have the most advanced knitters eager to experiment. Bright color dominates throughout this exuberant book, making simple patterns boldly stand out. Discover vibrant color, in-depth instruction, and artful inspiration that have ruled Christoffersson's work and life. Pop Knitting promises revolutionary knitting results. "--